Development of polydimethylsiloxane-based biomimetic scaffolds with cylinder micropillars for retinal pigment epithelial cell cultivation. Issue 11 (7th September 2020) - Lin, Yi-Ying; Yang, Yi-Ping; Lai, Wei-Yi; Chien, Chian-Shiu; Chen, Shih-Jen; Hwang, De-Kuang; Lai, Ying-Hsiu; Lin, Tai-Chi; Chiou, Shih-Hwa; Lo, Yu-Li; Huo, Teh-Ia; Chien, Yueh
Abstract : Background: Age-related macular degeneration (AMD) is one of the leading causes of vision loss. Once the retinal pigment epithelium (RPE) layers are destroyed, the poor visual acuity and recognition are generally irreversible. Cell therapy that possesses enormous potential in regenerative medicine may provide an alternative treatment for several incurable diseases such as AMD. In this study, we developed an innovative polydimethylsiloxane (PDMS)-based biomimetic scaffolds with cylinder micropillars for the cultivation of induced pluripotent stem cell–derived RPEs (iPSC-RPEs). RPEs were cultured on the PDMS-based biomimetic scaffolds and validated the cells gene expression. Methods: The biomimetic PDMS scaffold was fabricated through spin coating and lithography method. It was further modified on surface with biomolecules to improve cell affinity and stability. The iPSC-RPEs were seeded on the scaffold and analyzed with characteristic gene expression. Results: PDMS biomimetic scaffold was analyzed with Fourier transform infrared spectroscopy and proved its chemical composition. iPSC-RPEs demonstrated confluent cell monolayer on the scaffold and maintained RPE-specific gene expression, which proved the PDMS-based biomimetic scaffold to be supportive for iPSC-RPEs growth. Conclusion: The PDMS interface allowed regular growth of iPSC-RPEs and the design of cylinder micropillars further provided the bioscaffold high motion resistance may improve the engraftment stability of iPSC-RPEs after transplantation. Taken together, this innovative PDMS-based biomimetic scaffold may serve as an ideal interface for in vitro iPSC-RPE cultivation and subsequent transplantation in vivo. This novel device exhibits better bioavailability than conventional injection of donor cells and may be an alternative option for the treatment of AMD.